Alpha 1-Adrenoceptor Blocker May Improve Not Only Voiding But Also Storage Lower Urinary Tract Symptoms Caused by 125I Brachytherapy for Prostate Cancer. (30th March 2014) - Oyama, Nobuyuki; Aoki, Yoshitaka; Ito, Hideaki; Miwa, Yoshiji; Akino, Hironobu; Sato, Yoshitaka; Shioura, Hiroki; Kimura, Hirohiko; Yokoyama, Osamu
Abstract : Purpose . To assess changes in lower urinary tract symptoms (LUTS) within 1 year after brachytherapy in patients receiving alpha 1-adrenoceptor antagonists. Methods . We retrospectively evaluated 116 patients who underwent 125 I prostate brachytherapy in our institute. Seventy-one patients were treated with a combination of external beam radiation therapy and brachytherapy. Alpha 1-adrenoceptor antagonists were prescribed to all patients after brachytherapy. International Prostate Symptom Score (IPSS) forms and postvoid residual urine volume were recorded at all follow-up visits. Results . Forty-nine patients were given tamsulosin hydrochloride, 32 were given silodosin hydrochloride, and 35 were given naftopidil for up to 6 months after seed implantation. Patients given tamsulosin or naftopidil tended to show a higher peak IPSS and slower recovery to baseline values than those given silodosin. The patients given naftopidil showed an insufficient recovery in storage symptoms in naftopidil group in comparison with tamsulosin group at 3 months and with silodosin group at 6 and 9 months. Conclusions . In the management of LUT after brachytherapy, silodosin may provide a more favorable improvement. Silodosin and tamsulosin may have an advantage in improving not only voiding but also storage lower urinary tract symptoms after brachytherapy.